Evidence That Non-Syndromic Familial Tall Stature Has an Oligogenic Origin Including Ciliary Genes - Weiss, Birgit; Eberle, Birgit; Roeth, Ralph; de Bruin, Christiaan; Lui, Julian C.; Paramasivam, Nagarajan; Hinderhofer, Katrin; van Duyvenvoorde, Hermine A.; Baron, Jeffrey; Wit, Jan M.; Rappold, Gudrun A. (Frontiers in Endocrinology, 2021)
Human growth is a complex trait. A considerable number of gene defects have been shown to cause short stature, but there are only few examples of genetic causes of non-syndromic tall stature. Besides rare variants with large effects and common risk alleles with small effect size, oligogenic effects may contribute to this phenotype. Exome sequencing was carried out in a tall male (height 3.5 SDS) and his parents. Filtered damaging variants with high CADD scores were validated by Sanger sequencing in the trio and three other affected and one unaffected family members. Network analysis was carried out to assess links between the candidates, and the transcriptome of murine growth plate was analyzed by microarray as well as RNA Seq. Heterozygous gene variants in CEP104, CROCC, NEK1, TOM1L2 and TSTD2 predicted as damagingwere found to be shared between the four tall family members.Three of the five genes (CEP104, CROCC and NEK1) belong to the ciliary gene family. All genes are expressed in mouse growth plate. Pathway and network analysis indicated close functional connections. Together, these data expand the spectrum of genes with a role in linear growth and tall stature phenotypes.